2004
DOI: 10.1007/s00330-004-2456-4
|View full text |Cite
|
Sign up to set email alerts
|

MRI in coronary artery disease

Abstract: Diagnosis of coronary artery disease (CAD) is a major challenge for medical imaging, because CAD is the leading cause of death in developed nations. Several non-invasive tests are used in clinical routine for the detection of CAD. However, due to limited sensitivity and specificity, the reliable diagnosis as well as the exclusion of CAD can only be established by catheter angiography. In patients with known CAD, therapeutic decisions require accurate information on myocardial function, ischemia and viability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
(43 reference statements)
0
11
0
3
Order By: Relevance
“…BB techniques are not limited to providing data on LV mass in cardiac MR; advantages have also been shown for the assessment of the coronary arteries (MRCA) [16]. Bright blood techniques have several limitations in MR angiography (MRA), including difficulty identifying luminal stenosis, as turbulent blood flow can appear as artifactual darkening.…”
Section: Discussionmentioning
confidence: 99%
“…BB techniques are not limited to providing data on LV mass in cardiac MR; advantages have also been shown for the assessment of the coronary arteries (MRCA) [16]. Bright blood techniques have several limitations in MR angiography (MRA), including difficulty identifying luminal stenosis, as turbulent blood flow can appear as artifactual darkening.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary MR-angiography has been demonstrated to be a useful technique for non-invasive visualization of the major epicardial vessels and for detection of coronary artery stenoses [1][2][3][4][5][6][7][8]. However, its clinical utility has been limited by several major obstacles, including compensation for cardiac and respiratory motion and the need for higher spatial resolution.…”
Section: Introductionmentioning
confidence: 98%
“…In one single scheduled appointment, CMR may assess morphology, function, myocardial tissue characterization and myocardial perfusion [54].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Still, previous studies comparing the diagnostic value of MPS and CMR [56,57] have shown CMR to perform well. CMR may display perfusion, wall motion and LGE in one appointment [54]. The diagnostic accuracy from CMR first-pass perfusion increases when the information from LGE images is added to the evaluation.…”
Section: Image Qualitymentioning
confidence: 99%